"Place": Classrooms and Cyberspace–A Discourse Analysis of How Place Shapes Interaction and Learning - Hyungmi Hyun; Susan Strauss (Adult Education Research Conference, 2001)
This is a cross-environmental study focusing on how interactants in two distinct learning settings communicate and engage in course-related planning and problem solving-activities as members of their particular academic community. One setting is a face-to-face class; the second is the identical course offered on-line. The primary methodological approach is discourse analysis.